P320 Combined mesenchymal stromal cells and anti-cytokine therapy of perianal Crohn's disease. (27th May 2021) - Knyazev, O; Kagramanova, A V; Lishchinskaya, A; Shkurko, T; Li, I; Parfenov, A
Abstract: Background: Perianal fistulas are common types of fistulas in Crohn's disease (CD). Mesenchymal stromal cells (MSC), which have immunomodulatory properties and high regenerative potential, are currently also used for the treatment of fistula CD. The purpose of this study was to compare the effectiveness of combined therapy (local and systemic) mesenchymal stromal cells (MSC) of bone marrow, in the effectiveness of combination therapy MSC (local administration) and infliximab (IFX), as therapy the IFX with immunomodulators on the healing of simple perianal fistulas in Crohn's disease (CD). Methods: Seventy-five patients with CD with perianal lesions were divided into three groups depending on the method of therapy. The first group of СD patients aged 19 to 59 years (Me-29) (n=25) received a culture of MSC systematically according to the scheme and locally. The second group of patients with CD (n=25) aged 20 to 60 years (Me-28) received anti-cytokine therapy with IFX and immunomodulators. The third group of patients with CD (n=25) aged 20 to 62 years (Me-30) received MSC systemically and locally, as well as anti-cytokine therapy with IFX. The dynamics evaluated the complete closure of the external opening of the fistula. Ano-and rectosigmoscopy was performed 2 and 12 months after the start of therapy. The comparative analysis was performed using four-field tables using nonparametric statistical criteria. Results: After 2 months in the first group of patients, healing of simple fistulas was observed in 15/25 (60.0%), in the third group-22/25 patients (88.0%) (RR–1.467; 95% CI - 1.032-2.084; x 2 = 3.742; p=0.02948). After 2 months in the second group, healing of simple fistulas was observed in 16/25 (64.0%) (RR-1.37; 95% CI 0.991-1.908; x 2 =4.091; p=0.056). After 12 months in the first group of patients, healing of simple fistulas was observed in 17/25 (68.0%), in the third group-24/25 (96.0%) patients (RR 1.412; 95% CI 1.066–1.869; x 2 =7.399; p=0.0124). After 12 months in the second group, healing of simple fistulas occurred in 18/25 (72.0%) (RR -0.750; 95% CI 0.580– 0.970; x 2 =5.922; p=0.0488). Conclusion: Combined cells and anti-cytokine therapy of CD with perianal lesions contributes to more frequent and prolonged closure of simple fistulas, compared with MSC monotherapy and IFX monotherapy.